Study on the impact of mining and agricultural activities on Tasik Chini water quality - Che Fatin Fatiha, Che Man (2017)
A study was conducted at selected area of the Tasik Chini to determine the water quality due to the activities around the study area. The water samples were collected from Laut Melai, Laut Gumum and Laut Kenawar which are located in mining, agricultural and constant area. The water samples were taken from September until November 2017. The samples were taken two times during this study. There are two types of testing in this study which are in – situ and ex-situ testing. In – situ test parameters were such as pH, temperature, turbidity, electrical conductivity and dissolved oxygen while the ex-situ such as biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammoniacal nitrogen (NH3-N), phosphorus, total suspended solid (TSS) and heavy metals lead, chromium, cadmium, nickel and copper. All the parameters were analysed and measured according to Water Quality Index (WQI) and National Water Quality Standard (NWQS) for Malaysia. Based on the National Water Quality Standards (NWQS), the mean value of temperature is categorized within normal range while pH, turbidity, NH3-N, TSS, BOD, COD and EC are categorized under Class I at all stations. Parameter DO is categorized in Class IIB at Kenawar station and Class III at Gumum and Melai stations. Meanwhile for all types of heavy metal are classified under Class II except Nickel. Based on Water Quality Standards (WQI), the calculation WQI value are 86.66 mg/L, 87.93 mg/L, and 84.56 mg/L at Gumum, Kenawar and Melai stations respectively which are categorized under Class II. Tasik Chini is suitable for recreational activity and body contact is allowed, however basic treatment required for water supply. The mining and agricultural activities was affected the quality of water but do not bring harmful to the ecosystem of Tasik Chini because the result indicate the water quality only slightly polluted.